Caffeine and exercise: What next? - Pickering, C.; Grgic, J. (Sports Medicine, 2019)
Caffeine is a widely utilized performance-enhancing supplement used by athletes and non-athletes alike. In recent years, a number of meta-analyses have demonstrated that caffeine`s ergogenic effects on exercise performance are well-established and well-replicated, appearing consistent across a broad range of exercise modalities. As such, it is clear that caffeine is an ergogenic aid—but can we further explore the context of this ergogenic aid in order to better inform practice? We propose that future research should aim to better understand the nuances of caffeine use within sport and exercise. Here, we propose a number of areas for exploration within future caffeine research. These include an understanding of the effects of training status, habitual caffeine use, time of day, age, and sex on caffeine ergogenicity, as well as further insight into the modifying effects of genotype. We also propose that a better understanding of the wider, non-direct effects of caffeine on exercise, such as how it modifies sleep, anxiety, and post-exercise recovery, will ensure athletes can maximize the performance benefits of caffeine supplementation during both training and competition. Whilst not exhaustive, we hope that the questions provided within this manuscript will prompt researchers to explore areas with the potential to have a large impact on caffeine use in the future.